Both nutrients and macrophytes regulate organic carbon burial: Insights from high-resolution spatiotemporal records of a large shallow lake (Baiyangdian) in eastern China - Mao, Xin; Zhao, Hongmei; Kattel, Giri; Jiang, Gaolei; Ji, Yunping; Liu, Taibei; Yang, Jingsong; Liu, Zhe; Wang, Chengmin; Zhao, Hua; Liu, Linjing; Dong, Qiuyao (The Science of the total environment, 2024)
Both ecological regime shifts and carbon cycling in lakes have been the subject of global debates in recent years. However, the direct linkage between them is poorly understood. Lake Baiyangdian, a representative large shallow lake with the coexistence of a macrophyte-dominated area (MDA) and an algae-dominated area (ADA) in eastern China, allowing better understanding of the relationship between regime shifts and organic carbon (OC) burial in lakes. On the basis of Bayesian isotopic mixing modelling of C/N ratios and δ13C values, the sediment OC is primarily of autochthonous origin. The mean OC burial rate (OCBR) was 39 g C m−2 yr−1 before eutrophication occurred in 1990 and increased approximately 2.7-fold to 106 g C m−2 yr−1 after eutrophication. Partial least squares path modelling revealed that this change can be largely attributed to enhanced primary productivity and rapid burial as a result of intensified human perturbation. In terms of spatial patterns, the OCBR was greater in the MDA than in the ADA, which may be related to the different burial and mineralization processes of debris from macrophytes and algae. It then deduced that a decrease in the OCBR and an increase in the mineralization rate might have occurred after a shift from a macrophyte-dominated state to an algae-dominated state. Our findings highlight that eutrophication generally increases OC burial by enhancing lake primary productivity. However, once nutrient levels reach a critical range, lake ecosystems may shift from a macrophyte-dominated state to an algae-dominated state, which can lead to a significant reduction in the carbon burial capacity of lakes. Therefore, more attention should be given to avoiding shifts in eutrophic lakes, as such shifts can alter carbon cycling. [Display omitted] •The average whole-lake OCBR increased by 2.7 times with eutrophication.•The OCBR was higher in the MDA than in the ADA.•OC burial capacity could decrease when the ecosystem undergoes a regime shift.